PERBEDAAN GENDER, KARAKTERISTIK PERUSAHAAN, DAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Marlyn Meliantha; Tjhai Fung Jin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to determine the effect of Return on Assets, board of director’s size, board of director’s independence, leverage, firm age, firm size, and gender diversity on the corporate social responsibility disclosure. The research data consist of 65 manufacturing companies listed on the Indonesian Stock Exchange consistently from 2017 to 2020 which are selected by purposive sampling method. This study uses multiple linear regression to analyze the data. The results of this study indicate that leverage, company size, and gender diversity affect the corporate social responsibility disclosure, while Return on Assets, size of the board of directors, independence of the board of directors, and company age have no effect on corporate social responsibility disclosure